2018
DOI: 10.1002/aic.16141
|View full text |Cite
|
Sign up to set email alerts
|

Validation study on spatially averaged two‐fluid model for gas‐solid flows: II. Application to risers and fluidized beds

Abstract: In our prior study (Schneiderbauer, AIChE J. 2017;63(8):3544-3562), a spatially averaged two-fluid model (SA-TFM) was presented, where closure models for the unresolved terms were derived. These closures require constitutive relations for the turbulent kinetic energies of the gas and solids phase as well as for the subfilter variance of the solids volume fraction. We had ascertained that the filtered model do yield nearly the same time-averaged macroscale flow behavior in bubbling fluidized beds as the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
(147 reference statements)
0
35
0
Order By: Relevance
“…Moreover, in the literature, some studies suggested that the free slip 14,49 (e.g., specularity coefficient φ ≤ 0.001) or partial slip 9,18 condition is able to appropriately describe the particle–wall interactions in wall‐bounded FBs. Zhu et al 21,59 unveiled that coarse‐grid simulations with various particle‐wall slip conditions still could predict macroscopic flow characteristics reasonably well.…”
Section: Application Of ML Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in the literature, some studies suggested that the free slip 14,49 (e.g., specularity coefficient φ ≤ 0.001) or partial slip 9,18 condition is able to appropriately describe the particle–wall interactions in wall‐bounded FBs. Zhu et al 21,59 unveiled that coarse‐grid simulations with various particle‐wall slip conditions still could predict macroscopic flow characteristics reasonably well.…”
Section: Application Of ML Modelmentioning
confidence: 99%
“…Alternatively, subgrid models (SGMs) for interphase closure corrections such as the energy minimization multi‐scale (EMMS), 7‐9 filtered TFM (fTFM), 2,10‐15 spatially‐averaged TFM (SA‐TFM), 16‐18 and gradient‐based method, 19‐21 have been developed to account for effects of unresolved inhomogeneous structures. SGM enables a dramatic reduction of computational overhead by employing coarse grids while still maintaining high accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling particle‐laden flows is of major interest in developing a better understanding of these systems and, in an industrial context, improving process optimization, troubleshooting, and scale‐up. There has been a variety of approaches to modeling these systems including direct numerical simulation (DNS), Eulerian–Lagrangian (EL) simulation, and Eulerian–Eulerian (EE) simulation 1‐7 . One major challenge in doing so involves not only successfully resolving the features present but also doing so in a way that is computationally feasible and efficient 8,9 .…”
Section: Introductionmentioning
confidence: 99%